Formation of the digital space of Kazakhstan and the Central Asia countries in the conditions of industrial revolution - Duisen, G.M.; Aitzhanova, D.A. (BUKETOV BUSINESS REVIEW, 2018)
The paper considers the key directions of the use of information and communication technologies in the implementation of the principles of foreign policy of Kazakhstan and the countries of Central Asia. The importance of studying these issues in the conditions of digitalization of national economies is determined taking into account modern global challenges and changes in political, economic, technological and social character. The peculiarities and problems of the development of the digital economy in Kazakhstan are determined on the basis of the principles of the industrial revolution. Presented are systemic reforms and priority policies for the implementation of the Strategic Plan of Kazakhstan to 2025. It is noted that technological modernization will increase the productivity of economic entities, due to their competitiveness in foreign markets. It is shown that the new economy is based on the continuity of innovative development, and the applied developments and needs of the business environment must be closely interrelated, and new technologies must be based on fundamental studies. To develop a digital society, increase the literacy of the population, specialists and management personnel in the field of information and communication technologies are needed in the sectoral context. All this is in tandem with the development of the innovation of the ecosystem at the country level and further in the regional format and corresponds to the multi-vector nature of the foreign policy of the RK and the countries of Central Asia.